Natural convection of a hybrid nanofluid subjected to non-uniform magnetic field within porous medium including circular heater. Issue 4 (9th April 2019) - Izadi, Mohsen; Maleki, Nemat M.; Pop, Ioan; Mehryan, S.A.M.
Abstract : Purpose: This paper aims to numerically investigate the natural convection heat transfer of a hybrid nanofluid into a porous cavity exposed to a variable magnetic field. Design/methodology/approach: The non-linear elliptical governing equations have been solved numerically using control volume based finite element method. The effects of different governing parameters including Rayleigh number ( Ra = 10 3 − 10 6 ), Hartman number ( Ha = 0 − 50), volume fraction of nanoparticles ( φ = 0 − 0.02), curvature of horizontal isolated wall ( a = 0.85 − 1.15), porosity coefficient ( ε = 0.1 − 0.9) and Darcy number ( Da = 10 −5 − 10 −1 ) have been studied. Findings: The results indicate that at low Darcy numbers close to 0, the average Nusselt number Nua enhances as porosity coefficient increases. For a = 1 and a = 1.15 in comparison with a = 0.85, the stretching of the isothermal lines is maintained from the left side to the right side and vice versa, which indicates increased natural convection heat transfer for this configuration of the top and bottom walls. In addition, at higher Rayleigh numbers, by increasing the Hartmann number, a significant decrease is observed in the Nusselt number, which can be attributed to the decreased power of the flow. Originality/value: The authors believe that all the results, both numerical and asymptotic, are original and have not been published elsewhere.